A STUDY OF STUDENTS’ PERCEPTION: IDENTIFYING EFL LEARNERS’ PROBLEMS IN SPEAKING SKILL - Nadya Khoirunnisa; Yousef Bani Ahmad (IKIP Siliwangi, 2022)
Speaking skill is an important aspect of communication and must acquire when learning a foreign language. However, many English learners face problems in speaking. This study focused on the student’s perception of identifying problems and solutions encountered by EFL learners in speaking skill. This research was employed using case study methods in which participant of this research is twenty-seven students from one university in Indonesia. The technique to collect data is questionnaire. The finding showed that students as EFL learners faced problems in speaking English. 71,6% of students had faced problem at worrying making mistakes, worry being criticism, and feeling shy. Then, only 18.5% frequently participate in their classes. 96.3% of students lacked of subject knowledge and only 14.8% students are motivated to master the English language. Next, 81.5% of students agree that mother tongue is easier and they are speak in their mother tongue during English class. Keywords: EFL, Speaking Problems, Speaking Skill